Interactive Learning Media Based on Articulate Storyline in Social Sciences Learning for Grade V Elementary School - Kusuma, Dyah; Ahmadi, Farid (Universitas Pendidikan Ganesha, 2024)
The learning media owned by schools and used by teachers are still limited. Especially in technology-based interactive learning media, students become passive because the press used by teachers has not yet been interactive. This research aims to develop interactive learning media, Articulate Storyline, for Social Sciences lesson content on Various Economic Activities in Indonesia. This type of research was developed using the Borg and Gall research model. Observations, interviews, and questionnaires were used as data collection methods. Several experts and students carried out product design trials, including material experts, media experts, and small-scale tests carried out by student representatives. Qualitative and quantitative analysis are used as data analysis techniques. Research data shows that the percentage level of appropriateness for interactive learning media based on Articulate Storyline by material experts is 96.25%, and media experts are 96.66%. Based on the Normalized Gain test results, a score of 0.62 was achieved with quite effective qualifications. It was concluded that the development of interactive learning media based on Articulate Storyline is suitable for use for Social Sciences lesson content in the learning of fifth-grade elementary school students. The implication of this research is that interactive multimedia learning media is more effectively used in material on Various Businesses and Economic Activities in Indonesia.